PgRNA closely correlates to cytokine profile in HBeAg-positive pregnant women undergoing prophylactic antiviral intervention - Tang, Qiao; Wang, Chunrui; Li, Hu; Chen, Zhiwei; Liu, Xiaoqing; Xue, Yunling; Qiu, Yue; Zeng, Yi; Hu, Peng (Frontiers in Immunology, 2024)
BackgroundPrevious studies primarily focused on the effects of ALT and virology, but there is a lack of research on the correlations of HBcrAg and pgRNA, two novel virologic markers, with immunological parameters in pregnant women with CHB undergoing prophylactic antiviral intervention.MethodsWe conducted a retrospective cohort study involving 28 HBeAg-positive pregnant women with CHB undergoing prophylactic antiviral intervention. Clinical data, virological markers (HBV DNA, HBsAg, HBeAg, HBcrAg and pgRNA) and 28 cytokines were detected at three time points: 24-28 weeks gestation (before prophylactic antiviral intervention), near birth and within 3 months postpartum.ResultsPgRNA was moderately (correlation coefficient between 0.4 and 0.6) positively correlated with Th1-type cytokines (IFN-γ, IL12p70, IL2, and TNF-α), Th17-type cytokines (IL21), Th2-type cytokines (IL10, IL4, and IL5), and cytokines regulating cell proliferation and differentiation (CTLA4, IL15, IL23, and TGF-β1) and moderately negatively correlated with EGF (correlation coefficient = -0.4), while ALT, HBV-DNA, HBsAg and HBcrAg were insignificantly correlated with cytokines at 24-28 weeks of gestation. Most cytokines tended to be elevated, with statistically significant increases observed only for the chemokines IP10 and MCP-1 during pregnancy. Most cytokines were significantly increased in postpartum women with virologic rebound after treatment discontinuation postpartum, but no significant change in the Th1/Th2 ratio. Changes in virologic markers were significantly correlated with cytokines. Immune activation was more pronounced in postpartum women who developed ALT flare compared to who did not, with Th1-type cytokines (especially IL12p40) and chemokines being main differential cytokines.ConclusionPgRNA was more closely correlated with cytokine profiles, and postpartum ALT flare may be the result of the interaction between Th1-type cytokines and chemokines.